ANALISIS PENILAIAN KINERJA MENGGUNAKAN METODE BALANCED SCORECARD PADA PERUSAHAAN SEKTOR ASURANSI SEBELUM DAN SEMASA COVID (2020-2022) - Arif Iman Santoso; Yeni Elfiza Abbas (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Company performance appraisal really helps management in assessing the extent to which the company has done in achieving the company's strategy and vision and mission. Company performance can be assessed using the balanced scorecard method in which this method uses four perspectives to assess company performance, namely a financial perspective, a customer perspective, an internal business perspective, and also a learning and growth perspective. The balanced scorecard method does not only assess the financial aspects but also non-financial aspects. The purpose of this study was to assess company performance before and during the Covid 19 pandemic using the balanced scorecard method for companies engaged in the insurance sector. This study uses secondary data, namely financial reports and annual reports for 2020 and 2021. Based on data processing, the results show that from the four perspectives used, the financial perspective has decreased significantly. From the customer perspective, the results obtained show an increase because the benefits of the products produced can be felt by consumers so that more and more awards are obtained. From an internal business perspective, there was a decrease in achievement due to the difficulty for companies to make new products during the Covid 19 pandemic. From a learning and growth perspective, it experienced a decrease due to the difficulty for companies to conduct face-to-face training so that it was difficult to maximize employee training.